EFEKTIVITAS BELAJAR DARI RUMAH DI TENGAH PANDEMI COVID-19 - Dwi Cahyadi Wibowo; Yuliana Deta; Olenggius Jiran Dores (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2020)
The aim of this study was to describe students' responses to the effectiveness of learning from home, since world pandemic of Covid-19. The research method used was descriptive quality research methods. The research subjects were 24 students of class VB, the homeroom teacher of class VB, and 6 parents of class students. The data collection used were questionnaires, interviews, and documentation. The results of this study is : First, the student's response to the effectiveness of learning from home during the Covid-19 pandemic percentage score of 72.35% so it is included in the Good category. Second, the factors that become obstacles are health, interest, school, and physical environmental. Third, the efforts of teachers and parents are collaborating intensively; giving directions to children how behavior is used as examples; preparing study schedules; giving rewards; being friends and discussion partners; condition teaching and learning to use the online system; assignments are given in the form of worksheet; instill ways to maintain interpersonal relationships; provide ways of overcoming emotional behavior; provide effective learning instructions; provide opportunities for independent learning; do not turn on television when children learn; and discuss the rules of learning at home.